Pengaruh Pemberdayaan Dana Zakat Produktif Terhadap Kesejahteraan Umat - Sabik Khumaini (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2018)
Zakat is one of the Islamic characteristics of the economic system, it is also one of the most effective instruments to unite humanity to help each other against the problems of poverty through respective social lives. This research was conducted to examine the effect of empowerment of Productive Zakat Funds, managed by BAZNAS, on the welfare of the people. The use of analysis technique is Simple Regression and Hypothesis Testing using T-Statistics to test the Partial Regression coefficient with a level of significance of 5%. In addition, a Classic Assumption test that includes Normality Test, Heteroscedasticity Test, and Autocorrelation Test is also carried out. During the observation period for July 2015- December 2017, the results of the study did not find any deviation from classical assumptions, this indicates that the available data have fulfilled the requirements to use the Simple Regression Equation Model. The results of the analysis show that Productive Zakat Funds have a positive and insignificant effect on the welfare of the people as measured by the CIBEST Welfare Index, with a level of significance greater than 5%. Zakat merupakan salah satu ciri dari sistem ekonomi Islam, Zakat adalah salah satu instrumen yang paling efektif untuk menyatukan umat manusia untuk saling membantu permasalahan kemiskinanan dalam kehidupan sosial masing-masing. Penelitian ini dilakukan untuk menguji pengaruh pemberdayaan dana zakat produktif yang dikelola oleh BAZNAS terhadap kesejahteraan umat. Teknik analisis yang digunakan adalah regresi sederhana dan uji hipotesis menggunakan t-statistik untuk menguji koefisien regresi parsial dengan level of significance 5%. Selain itu juga dilakukan uji asumsi klasik yang meliputi uji normalitas, uji heteroskedastisitas dan uji autokorelasi. Selama periode pengamatan periode Juli 2015- Desember 2017 hasil penelitian tidak ditemukan adanya penyimpangan asumsi klasik, hal ini menunjukkan bahwa data yang tersedia telah memenuhi syarat untuk menggunakan model persamaan regresi sederhana. Dari hasil analisis menunjukkan bahwa dana zakat produktif berpengaruh positif tidak signifikan terhadap kesejahteraan umat yang diukur dengan Indeks Kesejahteraan CIBEST dengan level of significance lebih besar dari 5%.